Analisis Kesuksesan Penerapan Sistem informasi Kepegawaian pada sekretariat jenderal kementerian energi dan sumber daya mineral - , Joko Raharjo, S.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The implementation of system and information technology (SIT) to support activities in an organization require significant costs, coupled with the possibility of failure. But simultaneously, the application of SIT also provides an opportunity of technological transformation, increased productivity and speed of service. Secretariat General of the Ministry of Energy and Mineral Resources has also applied SIT in the work environment, one of which is Human Resources Information System (SIPEG). The authors do research to see how the perceptions of employees within the Secretariat General of the Ministry of Energy and Mineral Resources in assessing SIPEG success in supporting its work. How employee perceptions of the system quality, information quality, service quality, user satisfaction, utilization, and net benefits will be examined. Research carried out by using the Information System Success Model. The results showed that the success of SIPEG largely determined by the quality of the system and quality of information. Quality of service is not so decisive because the user is more concerned with the system quality and information quality rather than the speed of the system in response to user actions, or rather than the solution given if there are problems with the system